Meningkatkan Hasil Belajar Perkalian Matematika Siswa Kelas V di Sekolah Inklusi dengan Penerapan Metode Jarimatika - Oktaviana Dwi Ardianingtyas; Vivi Rulviana; Rakini Rakini (Lembaga Pengembangan Kinerja Dosen, 2024)
The goal of this study is to improve the mathematics learning outcomes of fifth-grade students in inclusive schools by applying the Jarimamatics approach of multiplying numbers from 6 to 9. This research was carried out at SDN 02 Taman Kota Madiun. The study method employed is Classroom Action study (PTK), which is conducted in two cycles. Each cycle includes planning, implementation, observation, and reflection. The subjects of this study were all eight class V pupils.Tests, observations, and documentation are some data collection approaches. The Jarimatika technique was used in this research to improve learning outcomes in mathematical multiplication. According to research data, the use of the Jarimatika technique can improve the multiplication skills of class V students. This is proven by an increase in student learning completion by 37.5% from cycle I to 75% in cycle II. Thus, using the Jarimatika approach can increase the accuracy of multiplication calculations for class V inclusive children. It is hoped that teachers can use the Jarimatika technique to improve mathematics learning in subsequent learning materials.